The effect of foreign competition on family and network labour allocation - Margaryta Klymak (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
This paper examines whether foreign competition affects the reallocation of unpaid and family workers from household businesses to working outside of the family firm. Using a rich panel dataset of Vietnamese manufacturing enterprises that went through trade liberalization, I find that import competition leads to the switching of family and unpaid employees from working at the household firm to working externally. This response to heightening foreign competition is also greater for less financially stable firms, and for the households largely reliant on the income from the household firm. This finding is consistent with income diversification on the part of households who own firms threatened by import competition. We also explore heterogeneous effects among entering and exiting firms, as well as industry-switching firms.
Keywords: D22; F16; O12; 330; family workers; foreign competition; household firms; unpaid labour